Hyperspectral Evaluation of the Human Liver During Major Resection. Issue 2 (19th June 2022) - Sucher, Elisabeth; Sucher, Robert; Guice, Hanna; Schneeberger, Stefan; Brandacher, Gerald; Gockel, Ines; Berg, Thomas; Seehofer, Daniel
Abstract : Objective: This study investigates the effects of PVE and vascular inflow control (VIC) on liver microperfusion and tissue oxygenation using hyperspectral imaging (HSI) technology. Background: Mechanisms triggering future liver remnant (FLR) augmentation introduced by PVE have not been sufficiently studied in humans. Particularly, the arterial buffer response (ABR) of the liver might play a vital role. Methods: Hyperspectral datacubes (TIVITA) acquired during 58 major liver resections were qualitatively and quantitatively analyzed for tissue oxygenation (StO2 %), near-infrared (NIR) perfusion, organ-hemoglobin indices (OHI), and tissue-water indices (TWI). The primary study endpoint was measurement of hyperspectral differences in liver parenchyma subject to PVE and VIC before resection. Results: HSI revealed parenchyma specific differences in StO2 % with regard to the underlying disease ( P < 0.001). Preoperative PVE (n = 23, 40%) lead to arterial hyperoxygenation and hyperperfusion of corresponding liver segments (StO2 : 77.23% ± 11.93%, NIR: 0.46 ± 0.20[I]) when compared with the FLR (StO2 : 66.13% ± 9.96%, NIR: 0.23 ± 0.12[I]; P < 0.001). In a case of insufficient PVE and the absence of FLR augmentation hyperspectral StO2 and NIR differences were absent. The hyperspectral assessment demonstrated increased liver tissue-oxygenation and perfusion in PVE-segments (n = 23 cases) and decreased total VIC in nonembolized FLR hemilivers (n = 35 cases; P < 0.001). Intraoperative HSI analysis of tumor tissue revealed marked tumor specific differences in StO2, NIR, OHI, and TWI ( P < 0.001). Conclusions: HSI allows intraoperative quantitative and qualitative assessment of microperfusion and StO2 % of liver tissue. PVE lead to ABR-triggered tissue hyperoxygenation and cross-talk FLR augmentation. HSI furthermore facilitates intraoperative tumor tissue identification and enables image-guided liver surgery following VIC.